Psychological determinants of the individual’s propensity to manipulate in interpersonal interactions - Grebin, Nataliya (Journal of Education Culture and Society, 2020)
The article presents results of research on individuals with different levels of propensity to manipulate in interpersonal interactions. The objective of this empirical research is to determine psychological peculiarities of individuals with propensities to manipulate and also to determine psychological factors of the personal propensity to manipulate. Key variables of our research are propensity to manipulate (dependent variable) and a range of psychological parameters that describe personal, individual and topological, motivational, value- and orientational, sense and existential fields of personality as well as peculiarities of their manifestation in interpersonal interaction (independent variables)